Clinical Symptoms, Total Hemocyte Count, and Differential Hemocyte Count of Vaname Shrimp Infected with Acute Hepatopancreatic Necrosis Disease (AHPND) - Harlina, Harlina; Hadijah, Siti; Hamdillah, Andi; Saenong, Muhammad; Astari, Siti Aisyah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This study aims to analyze changes in clinical symptoms, Total Hemocyte Count (THC), and Differential Hemocyte Count (DHC) in healthy vannamei shrimp and those infected with AHPND. The research was conducted in May 2024 at the Biota and Environmental Engineering Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Muslim Indonesia. The method used was sampling with two treatments (T1 and T2) observed at seven time intervals: 0, 3, 6, 12, 24, 48, and 72 hours. The results showed that clinical symptoms of AHPND-infected vannamei shrimp included reddening of the body, red swimming legs, pale hepatopancreas, and abnormal tilted swimming patterns. THC values obtained in both treatments (T1 and T2) across all time intervals showed no significant differences (P>0.05). DHC analysis revealed that the highest hyaline cell count in T1 occurred at 6 hours (64.59%), while in T2, it occurred at 0 hours (65.97%). The highest granular cell count in T1 was observed at 3 hours (29.17%), while in T2, it was at 72 hours (47.67%). The highest semi-granular cell count in T1 was recorded at 0 hours (27.38%), while in T2, it was at 48 hours (54.38%).